OSBPL2 Is Required for the Binding of COPB1 to ATGL and the Regulation of Lipid Droplet Lipolysis - Wang, Tianming (iScience, 2020)
The accumulation of giant lipid droplets (LDs) increases the risk of metabolic disorders including obesity and insulin resistance. The lipolysis process involves the activation and transfer of lipase, but the molecular mechanism is not completely understood. The translocation of ATGL, a critical lipolysis lipase, from the ER to the LD surface is mediated by an energy catabolism complex. Oxysterol-binding protein-like 2 (OSBPL2/ORP2) is one of the lipid transfer proteins that regulates intracellular cholesterol homeostasis. A recent study has proven that Osbpl2(−/−) pigs exhibit hypercholesterolemia and obesity phenotypes with an increase in adipocytes. In this study, we identified that OSBPL2 links the endoplasmic reticulum (ER) with LDs, binds to COPB1, and mediates ATGL transport. We provide important insights into the function of OSBPL2, indicating that it is required for the regulation of lipid droplet lipolysis.